2020
DOI: 10.1007/s13300-020-00918-7
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Lumbar Sympathetic Blockade Enhances the Effect of Lumbar Sympatholysis on Refractory Diabetic Neuropathy: A Randomized Controlled Trial

Abstract: Introduction There are a number of options for the symptomatic treatment of peripheral neuropathy, but the overall treatment outcomes remain unsatisfactory. Methods A total of 60 patients with refractory diabetic neuropathy were randomly assigned to two groups. Patients in Group A were treated with computed tomography (CT)-guided sympathetic neurolysis with alcohol, and patients in Group B were treated with a combined therapy of CT-guided catheterization to achieve cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“… Yuan et al, 2009 133 RCT 18 I-A Visual analog scale 44% of participants in the treatment arm achieved a VAS reduction of 3 points within three-month post-procedure. Sympathetic nerve block or neurolysis Sun et al, 2020 130 RCT 60 I-A Visual analog scale Pain scores of all patients decreased significantly compared with pre-treatment values, with lower pain scores in those treated with combined therapy (neurolysis and continuous lumbar sympathetic block) compared to sympathetic neurolysis only. Skin temperature, capillary filling time and blood oxygen saturation level were significantly improved in all participants.…”
Section: Section 4 Alternative Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“… Yuan et al, 2009 133 RCT 18 I-A Visual analog scale 44% of participants in the treatment arm achieved a VAS reduction of 3 points within three-month post-procedure. Sympathetic nerve block or neurolysis Sun et al, 2020 130 RCT 60 I-A Visual analog scale Pain scores of all patients decreased significantly compared with pre-treatment values, with lower pain scores in those treated with combined therapy (neurolysis and continuous lumbar sympathetic block) compared to sympathetic neurolysis only. Skin temperature, capillary filling time and blood oxygen saturation level were significantly improved in all participants.…”
Section: Section 4 Alternative Approachesmentioning
confidence: 99%
“… 129 Another RCT suggested combining treatment with continuous lumbar sympathetic block followed by alcohol neurolysis provided more benefit in pain scores versus sympathetic alcohol neurolysis alone, with benefits sustained at 6 months post treatment. 130 Similarly, another RCT compared alcohol neurolysis with radiofrequency thermocoagulation or both for treatment of PDN. Postoperative pain scores were significantly decreased from baseline with a 66.7%, 73.3% and 93.3% complete remission rate, respectively, without severe complications.…”
Section: Section 4 Alternative Approachesmentioning
confidence: 99%
“…More and more evidence showed that sympathetic nerve blockade for DPN can lastingly provide durable pain relief and increase skin temperature on the affected extremity. LSGB mainly dilates peripheral blood vessels of the lower limb through nerve block, increases blood flow, improves local microcirculation, promotes the establishment of collateral circulation, and plays an important role in preserving limbs 41,42 . Furthermore, the data show that the morbidity of phantom limb pain (PLP) in amputees ranged from 42% to 78%.…”
Section: Application Of Lsgb In Lower Limb Painmentioning
confidence: 99%
“…Contrastingly, the postprocedural increase in popliteal arterial velocity was not maintained after botulinum toxin injection. Sun et al 29 reported that chemical neurolysis, as well as continuous lumbar sympathetic ganglion block with local anesthetic and dexamethasone, enhanced peripheral microcirculation by improving skin temperature, capillary filling time, and blood oxygen saturation. Most likely, measurement of the peak systolic velocity in the popliteal artery could not reflect the capillary microcirculation changes.…”
Section: Pain Medicinementioning
confidence: 99%
“…Most likely, measurement of the peak systolic velocity in the popliteal artery could not reflect the capillary microcirculation changes. In addition, Sun et al 29 reported that chemical lumbar sympathetic ganglion neurolysis decreased plasma norepinephrine, serotonin, and substance P levels in patients with diabetes. Further studies are warranted to determine whether botulinum toxin injection onto the lumbar sympathetic ganglia can reduce these vasoactive and pain-modulating mediators.…”
Section: Pain Medicinementioning
confidence: 99%